Factors that influence the occurrence nutrition bad for toddlers in the Regency Kolaka, Indonesia - Selvia Selvia; Devi Savitri Effendy (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Background: Malnutrition remains a critical nutritional challenge in Indonesia, particularly among toddlers, who are highly susceptible. One of the direct causes of malnutrition is inadequate nutrient intake. Insufficient consumption of energy, protein, and fats can lead to suboptimal nutrient absorption and increased vulnerability to infectious diseases. Objective: This study aims to analyze the factors associated with malnutrition among children under five in Kolaka Regency. Methods: This research employed an observational analytic design using a case-control approach. The sample consisted of 82 participants from Kolaka Regency, Southeast Sulawesi Province. Data collection involved anthropometric measurements to assess children's weight, alongside questionnaires and food consumption recall forms. Data were analyzed using the Chi-Square statistical test, with a significance level set at p<0.05. Results: The study revealed that over 64% of children under five had inadequate energy, protein, fat, and carbohydrate intake. While 54.9% of mothers had moderate to high education levels, 69.5% of the environmental conditions were found to be below standard. Significant associations were identified between malnutrition and energy intake (p=0.000), protein intake (p=0.000), fat intake (p=0.000), carbohydrate intake (p=0.000), Vitamin A (p=0.000), iron (p=0.007), zinc (p=0.013), maternal education level (p=0.004), and environmental conditions (p=0.000). Conclusion: Malnutrition is significantly associated with factors such as energy, protein, fat, and carbohydrate intake, as well as levels of Vitamin A, iron, and zinc, maternal education, and environmental conditions. It is recommended to strengthen cross-sectoral collaboration and program coordination in addressing malnutrition, improve the capacity of nutrition workers through training, and involve community and religious leaders in tackling malnutrition. Keywords: Energy intake, protein, fat, carbohydrates, malnutrition, toddler environment